The Research of the School Education Contents Reformation: the Information Sources Aspect - Lidiya Pyrozhenko (Pedagogical Discourse, 2013)
The article studies the problem of classification of the source base for reformation of  school education contents during the period of 1964-1984, in particular, the criteria selected for grouping the source base, the level of information generalization, summarizing information aspects which the information source contains; the chronological criterion; the criterion of the subject of research (the sources of personalities study, scientific schools, pedagogical trends, separate educational institutions); nearness to the subject of the research. In the result of investigation the author has singled out the corresponding groups of sources that study the history of  general secondary education reformation in 1964-1984, which will form the basis for the research problem analysis.